ANALISIS KARAKTER PEDULI LINGKUNGAN SISWA SMA NEGERI DI KOTA PEKANBARU DENGAN PENERAPAN PROGRAM ADIWIYATA - Lasri Susanti; Yustina Yustina; Suwondo Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study was conducted to analyze the character of the environmental care of state high school students in Pekanbaru City by implementing the adiwiyata program, held from October 2018 to April 2019. This research uses the survey method. The parameters in this study are the character of environmental care in students. The data was obtained through a questionnaire that had been distributed to public high school class XI students in Pekanbaru City. The results showed that schools with independent adiwiyata levels were included in the good category with an average percentage of 2.90%. This school with independent adiwiyata level shows better results than national and city adiwiyata. with a percentage of 2.7% and 2.75% respectively. Based on the results of the study, independent level adiwiyata schools are categorized as good in forming the character of environmental care in students. While the national and city adiwiyata schools show that the character of the student's environment is categorized as sufficient.Key Words: Enviromental Care Character, Adiwiyata